A critical review of heat and mass transfer correlations for LiBr-H2O and NH3-H2O absorption refrigeration machines using falling liquid film technology - Narváez-Romo, Beethoven; Chhay, Marx; Zavaleta-Aguilar, Elí W. [UNESP]; Simões-Moreira, José R. (Elsevier, 2017)
This paper presents an extensive review of heat and mass transfer correlations in the framework of sorption machines operating based on the falling film technology, in which ammonia-water and lithium bromide-water are used as the working fluid pairs. Heat and mass transfer correlations are summarized as well as the application range and geometrical configuration. In order to compare the correlations found in the recent and classical literature, typical operation conditions for absorption refrigeration cycles have been adopted. Heat and mass transfer correlations have been evaluated for both working fluid pairs, mapping the possible heat and mass transfer values for refrigeration and air-conditioning applications. The study allowed comparing the two technologies using the same operational conditions. The ascertainment that the transfer correlations may behave differently has been showed. Finally, this work suggests that future researches about heat and mass transfer behavior should be to carry out for realistic operational condition of the absorption refrigeration cycles.
Keywords: Absorption; Ammonia-water; Falling film; Lithium bromide-water; Review